Natural gas potential of Neogene source rocks in the Yiliping area, Qaidam Basin: Using an improved hydrocarbon generation and expulsion model based on least‐squares Monte Carlo. Issue 5 (27th March 2023) - Li, Changrong; Lu, Hongxin; Shao, Lidong; Liu, Gang; Yang, Chun; Wang, Hairong; Huo, Zhipeng; Wang, Enze
Abstract : The Neogene petroleum system in the Yiliping area of the Qaidam Basin presents great prospects for natural gas exploration. However, its natural gas potential, including the source rock characteristics, is insufficient. Due to a lack of geological constraints, the hydrocarbon generation and expulsion (HGE) model, which is widely used in resource potential evaluation, may be unable to obtain optimal parameters. Here, we propose an improved HGE model based on least‐squares Monte Carlo to assess the HGE characteristics and natural gas resource potential of the Neogene source rocks in the Yiliping area by combining geological and geochemical investigations. The findings show that the Neogene source rock is effective and has significant potential for natural gas generation. Algae and bacteria, which were deposited in a saline and anoxic environment, are the primary sources of organic matter in Neogene source rock (primarily Type II and Type III). Modelling work suggests that Type II and III kerogen of Neogene source rock reach hydrocarbon generation threshold (HGT) at Ro = 0.38% and Ro = 0.49% and reach hydrocarbon expulsion threshold (HET) at Ro = 0.45% and Ro = 0.55%. The maximum HGE intensities are 3400 × 10 4 and 3378 × 10 4  t/km 2 . The extra‐source natural gas and shale gas resource potentials are predicted to be 2.05 × 10 12  m 3 to 4.11 × 10 12  m 3 and 7.03 × 10 12  m 3 . The findings will guide future Neogene natural gas exploration in the Yiliping area of the Qaidam Basin. Abstract : This study proposed an improved hydrocarbon generation and expulsion model based on least‐squares Monte Carlo. In conjunction with the analysis data, we first investigated the source rock potential, hydrocarbon generation and expulsion characteristics, and natural gas resource potentials of the Neogene petroleum.